2021
DOI: 10.1186/s13613-021-00972-9
|View full text |Cite
|
Sign up to set email alerts
|

Gas conditioning during helmet noninvasive ventilation: effect on comfort, gas exchange, inspiratory effort, transpulmonary pressure and patient–ventilator interaction

Abstract: Background There is growing interest towards the use of helmet noninvasive ventilation (NIV) for the management of acute hypoxemic respiratory failure. Gas conditioning through heat and moisture exchangers (HME) or heated humidifiers (HHs) is needed during facemask NIV to provide a minimum level of humidity in the inspired gas (15 mg H2O/L). The optimal gas conditioning strategy during helmet NIV remains to be established. Methods Twenty patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…By observing the ventilation time of the two groups, it was shown that the invasive ventilation time and total ventilation time of the study group were significantly shorter than those of the control group, indicating that sequential ventilation therapy could reduce the time of tracheal intubation, thereby reducing the invasive ventilation time [ 10 ]. In addition, the comparison of blood gas indexes at different time periods before and after treatment showed that the PH changes of the two groups were consistent and had no significant difference after treatment, indicating that both treatment methods could better maintain PH stability [ 11 ]. After different treatments, the blood oxygen value of the two groups increased, while the blood carbon dioxide value decreased, and the improvement of PaCO 2 and PaO 2 in the study group was significantly better than that in the control group.…”
Section: Related Workmentioning
confidence: 99%
“…By observing the ventilation time of the two groups, it was shown that the invasive ventilation time and total ventilation time of the study group were significantly shorter than those of the control group, indicating that sequential ventilation therapy could reduce the time of tracheal intubation, thereby reducing the invasive ventilation time [ 10 ]. In addition, the comparison of blood gas indexes at different time periods before and after treatment showed that the PH changes of the two groups were consistent and had no significant difference after treatment, indicating that both treatment methods could better maintain PH stability [ 11 ]. After different treatments, the blood oxygen value of the two groups increased, while the blood carbon dioxide value decreased, and the improvement of PaCO 2 and PaO 2 in the study group was significantly better than that in the control group.…”
Section: Related Workmentioning
confidence: 99%
“…In one recent study, a double-tube circuit with no humidification allowed adequate conditioning of inspired gas, optimal comfort, and improved patient–ventilator interaction. [ 74 ] The use of heated humidifiers or HME in this setting resulted in increased discomfort due to excessive heat and humidity in the interface, which was associated with more intense dyspnea. [ 74 ] Humidification may be necessary when fresh gas flows >40 L/min are applied.…”
Section: Nivmentioning
confidence: 99%
“…[ 74 ] The use of heated humidifiers or HME in this setting resulted in increased discomfort due to excessive heat and humidity in the interface, which was associated with more intense dyspnea. [ 74 ] Humidification may be necessary when fresh gas flows >40 L/min are applied. [ 75 ]…”
Section: Nivmentioning
confidence: 99%
“…Preliminary data seem to show that no humidification is needed during helmet NIV if the total system’s minute ventilation does not exceed a threshold of around 40 L/min, which is the case for hypoxemic patients treated with helmet NIV. A double-tube circuit without any humidification reduces discomfort and provides sufficient conditioning of the inspired gas, without any effect on inspiratory effort and work of breathing [ 69 ].…”
Section: Specific Settingsmentioning
confidence: 99%